2023
DOI: 10.3390/jcm12062401
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Adjuvant Therapy after Surgery for Colorectal Cancer Liver Metastases: A Systematic Review

Abstract: The liver is the most common site of colorectal cancer metastatic spread. Although metastasectomy is the gold standard for fit patients with resectable colorectal cancer liver metastases (CRLMs), their management after surgical treatment remains controversial. The objective of this systematic review was to collate the currently available data of the agents used in the adjuvant setting in order to define the most optimal therapeutic strategy. A systematic review of the literature was conducted by searching PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Currently, there is no consensus or standard regarding the selection of adjuvant therapy regimens and treatment duration following conversion resection for HCC. However, insights can be drawn from the postoperative adjuvant strategies for liver metastases from colorectal cancer, which typically involve maintaining the pre‐existing chemotherapy regimen for 6 months or adjusting drug dosages and shortening the course of chemotherapy based on patient tolerance 76 . A real‐world study by Pan et al 77 .…”
Section: Postoperative Adjuvant Therapy Following Conversion Resectio...mentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is no consensus or standard regarding the selection of adjuvant therapy regimens and treatment duration following conversion resection for HCC. However, insights can be drawn from the postoperative adjuvant strategies for liver metastases from colorectal cancer, which typically involve maintaining the pre‐existing chemotherapy regimen for 6 months or adjusting drug dosages and shortening the course of chemotherapy based on patient tolerance 76 . A real‐world study by Pan et al 77 .…”
Section: Postoperative Adjuvant Therapy Following Conversion Resectio...mentioning
confidence: 99%
“…However, insights can be drawn from the postoperative adjuvant strategies for liver metastases from colorectal cancer, which typically involve maintaining the pre‐existing chemotherapy regimen for 6 months or adjusting drug dosages and shortening the course of chemotherapy based on patient tolerance. 76 A real‐world study by Pan et al. 77 found that among advanced HCC patients who underwent FOLFOX‐HAIC‐based conversion therapy, receiving postoperative adjuvant therapy significantly improved long‐term survival outcomes, especially in patients with macrovascular invasion and positive hepatitis B surface antigen.…”
Section: Postoperative Adjuvant Therapy Following Conversion Resectio...mentioning
confidence: 99%
“…Liver resection remains the primary treatment for patients with colorectal cancer liver metastases. 1 However, more than 80% of these patients are not eligible for liver resection. 2 For patients with colorectal cancer liver metastases, Dueland et al 3 performed a 2-step liver transplant using the Resection and Partial Liver Segment 2/3 Transplantation With Delayed Total Hepatectomy (RAPID) procedure, which was first described by Line et al 4 in 2015 and demonstrated excellent clinical results.…”
mentioning
confidence: 99%
“…Liver resection remains the primary treatment for patients with colorectal cancer liver metastases . However, more than 80% of these patients are not eligible for liver resection .…”
mentioning
confidence: 99%